Boron-migration Mediated Photochemical Enantioselective Protonation/Deuteration via Chiral Hydrogen Bonding Catalysis - Ban, Xu; Jiang, Zhiyong (Synlett)
Enantioselective protonation/deuteration has emerged as pivotal transformations in modern synthetic chemistry, offering strategic control over stereochemistry at tertiary chiral carbon centers while enabling the selective incorporation of isotopic labels. Recent advancements in chiral catalysts, photochemical activation, and dual catalytic systems have significantly expanded the scope of enantioselective protonation/deuteration, allowing for efficient and sustainable protocols under mild reaction conditions. Herein, we disclose our recent progress on photochemical enantioselective protonation/deuteration via boron migration, which provides a robust and unified platform for the enantioselective construction of tertiary C–H stereocenters under precisely controlled chiral hydrogen-bonding catalysis. Beyond its capacity to incorporate protons or deuterium atoms, the expansion of the toolkit for chiral hydrogen-bonding catalysis and the application of boron migration in asymmetric synthesis represent two key innovations in this work, contributing to the development of more versatile asymmetric reactions.